Estudiantes de la carrera de Enfermería, de la Facultad de Ciencias de la Salud y del Ser Humano de la UEB, socializaron sus trabajos de investigación - Llivi Ruilova, Danny Vicente (2024)
Students from the Nursing program, from the Faculty of Health and Human Sciences of the UEB, shared their research work, which was attended by Dr. Silvana López Paredes, Dean; and the members of the evaluating panel. During the exhibitions, the students showed their knowledge acquired during their professional training, with the taking of the Oath, they were legally graduated as Graduates in Nursing.